Flora and Fauna in Danau Singkarak (Ecolinguistic Study) - Akmal; Dwi Widayati (LingLit Journal Scientific Journal for Linguistics and Literature, 2021)
This article is focused on the ecolinguistics which discusses about the ecology study and linguistic study. This study discusses about the flora and fauna around Dana Singkarak area. It aims to give the name of plantations and animals which live so long near the lake. The animals are also so a little and nearly endanger because many people search the animals and plantation. They find out some animals to sell in the market because the cost is expensive and the animals meats are so delicious and full of vitamins so that there are some animals that have endanger and difficult to find. Then the plantation also nearly endanger because there are so many pollutions either air pollution or water pollution that have made the humans as the predators of them. This search has found some the unique plantations. So in the context of preserving the habitat of flora and fauna around Danau Singkarak. Because of that, ecolinguistics is to rename the flora and fauna to write in the dokumen or library and it will be useful for the next generations.